2018
DOI: 10.1186/s13065-018-0370-0
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity, cytotoxic and antioxidant activities of Ricinus communis different parts

Abstract: Ricinus communis (castor plant) is a potent medicinal plant, which is commonly used in the treatment of various ailments. The present study was conducted to appraise the cytotoxicity and mutagenicity of R. communis along with antioxidant and antimicrobial activities. Cytotoxicity was evaluated by hemolytic and brine shrimp assays, whereas Ames test (TA98 and TA100) was used for mutagenicity evaluation. Plant different parts were extracted in methanol by shaking, sonication and Soxhlet extraction methods. The R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 69 publications
(49 reference statements)
1
18
0
Order By: Relevance
“…Fat and carbohydrate are good sources of energy for livestock and humans. Crude fibre content in diets have been reported to aid digestive processes; promoting health in livestock and humans (Abubakar et al, 2016) and these findings are in line with previous reports indicating the bioactivity and application of peels of various plants (Abbas et al, 2018;Abdel Aziz et al, 2018;Ahad et al, 2018;Derakhshan et al, 2018;Garrafa-Galvez et al, 2019;Gurumallesh et al, 2019;Hu et al, 2019;Jridi et al, 2019;Kharchoufi et al, 2018;Kokila et al, 2016;Lakkab et al, 2019;Liu et al, 2017;Rodsamran and Sothornvit, 2019;Xu et al, 2019).…”
Section: Resultssupporting
confidence: 88%
“…Fat and carbohydrate are good sources of energy for livestock and humans. Crude fibre content in diets have been reported to aid digestive processes; promoting health in livestock and humans (Abubakar et al, 2016) and these findings are in line with previous reports indicating the bioactivity and application of peels of various plants (Abbas et al, 2018;Abdel Aziz et al, 2018;Ahad et al, 2018;Derakhshan et al, 2018;Garrafa-Galvez et al, 2019;Gurumallesh et al, 2019;Hu et al, 2019;Jridi et al, 2019;Kharchoufi et al, 2018;Kokila et al, 2016;Lakkab et al, 2019;Liu et al, 2017;Rodsamran and Sothornvit, 2019;Xu et al, 2019).…”
Section: Resultssupporting
confidence: 88%
“…When increased quantity of H 2 O 2 is added to solution, then additional hydroxyl radicals are obtainable for oxidation of dye. As a result, there must be appropriate amount of H 2 O 2 for the effective dyes removal [22][23][24][25][26][27][28]. Therefore, H 2 O 2 should be introduced at an optimal concentration to obtain best degradation and the optimum concentration was 9% H 2 O 2 .…”
Section: Measurement Of Absorbancementioning
confidence: 99%
“…Consequently, in animal studies elevated plasma ALT and AST levels were found upon administration of ricin A chain, indicating hepatotoxicity and increasing inflammatory responses (Buonocore et al 2011). Finally, it has also been shown that seeds, stem, leaves and root methanolic extracts from Ricinus communis induced mild to moderate cytotoxicity against human or bovine red blood cells and also exerted mild mutagenicity (Abbas et al 2018).…”
Section: Mechanisms Of Ricin Actionmentioning
confidence: 99%